Nurses as Boundary Actors in Sustainable Health Care: A Discussion Paper - Joanna Law; Maya R. Kalogirou; Sherry Dahlke (York University Libraries, 2021)
The devastating global health impacts of climate change are becoming more apparent and more frequent. Health care systems are increasingly burdened by the response to these impacts. Paradoxically, as they respond to the negative health effects of climate change, these same resource intense health care systems are contributing to further climate change. Organizations and academics have issued a call to action for health care workers to mitigate climate change and promote environmental sustainability. Nurses are an integral part of health care systems but have been delayed in answering this call. In this paper we argue that nurses are particularly well suited to mitigating climate change in health care systems because their existing role is central to patient care, and as a result they interface with other health care providers and have developed proficiency in articulation work.